The effect of grocery item's packaging on the buying preference of UPV College of Management students and faculty
The study aims to know the effects of grocery items' packaging on the buying preference of consumers. This study was done through a survey conducted among 295 respondents in which 275 are students taking up BS Accountancy, BS Marketing, and BS Management, and the remaining 20 respondents are faculty members. According to findings, more than 85% of the respondents stated that the packaging of the product affects their buying preferences between two or more products of the same kind. In general, this study finds out that there is no significant difference between status, field of specialization/educational background, and sex as to the effects of packaging on their buying preferences.